2017
DOI: 10.1159/000456655
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Coccidioidomycosis Presenting as Carcinomatosis Peritonei and Intestinal Coccidioidomycosis in a Patient with HIV

Abstract: Coccidioidomycosis (CM) is a fungal infection endemic in southwestern regions of the United States, northwestern regions of Mexico, and some areas of Brazil and Argentina. Clinical presentation varies depending on the extent of the infection and the immune status of the host. The most common presentation ranges from flu-like symptoms to self-limiting pneumonia. Extrapulmonary presentations are uncommon and may involve the meninges, skin, and bone. Gastrointestinal and peritoneal involvement is extremely rare. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…One case demonstrated small bowel obstruction. Imaging may demonstrate ascites, mesenteric, or peritoneal caking thus prompting concerns of underlying malignancy, although the differential diagnosis of intra-abdominal caking should include the following: CM or other fungal diseases, tuberculosis (Tb), and carcinomatosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…One case demonstrated small bowel obstruction. Imaging may demonstrate ascites, mesenteric, or peritoneal caking thus prompting concerns of underlying malignancy, although the differential diagnosis of intra-abdominal caking should include the following: CM or other fungal diseases, tuberculosis (Tb), and carcinomatosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its presentation is more frequent in patients with risk factors that favor hematogenous dissemination, among which the male gender generally stands out in the context of immunosuppression. Taking into account that the most important role in protection is played by macrophages, which are only effective if the helper lymphocytes (CD4 +) are competent [7] , pregnant women, patients with active neoplastic processes and those with immunosuppression states (acquired immunodeficiency syndrome, lymphoma or transplant recipients especially) are more susceptible to presenting disseminated disease [1] , [8] . To date no immunological derangements have been documented in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…There have been previously documented cases of low-risk individuals developing DC. 3,9 Many cases reported that the progression of disease in these individuals was due to a delay in diagnosis at initial presentation. 9 Although our patient's treatment was not delayed, the duration of his treatment was inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, in some cases, macrophages that ingest the arthroconidia enter the lymphatic system and lead to disseminated disease. 3 The severity of disease can vary from mild to life-threatening disease. 4 The organs involved in disseminated disease include the skin, bones, joints, and central nervous system.…”
Section: Introductionmentioning
confidence: 99%